IgM anti-phenolic glycolipid I and IgG anti-10-kDa heat shock protein antibodies in sera and immune complexes isolated from leprosy patients with or without erythema nodosum leprosum and contacts - Rojas, R. E. (1997)
The aim of the present work was to evaluate the levels of anti-PGL-I and anti-10-kDa heat shock protein antibodies in serum and immune complexes isolated from leprosy patients, convivients and controls. Leprosy patients with erythema nodosum leprosum or without it were included and a comparative study was done to investigate intergroup differences. Immune complexes were precipitated from serum by polyethylene glycol 3.5%; antibody levels were measured in sera and in dissociated immune complexes by ELISA. Serum antibody levels were then correlated with immune complex-associated antibody levels. The results showed that the erythema nodosum leprosum group differed from controls, contacts and non-erythema patients in their immune complex levels. IgM anti-PGL-I and IgG anti-10-kDa heat shock protein antibodies were constituents of the immune complexes in patients with erythema nodosum leprosum, who exhibited a significant difference in their immune complex composition compared with controls, contacts and non-erythema patients; while free antibody levels (anti-PGL-I and anti-10-kDa) did not differentiate between erythema and non-erythema patients, the measurement of immune complex-associated antibodies demonstrated a significant difference between the two clinical conditions. Furthermore, the measurement of immune complex-associated anti-PGL-I IgM made it possible to differentiate between contacts and controls. The significance of these results is discussed.